High light‐induced hydrogen peroxide production in Chlamydomonas reinhardtii is increased by high CO2 availability. (March 2015) - Roach, Thomas; Na, Chae Sun; Krieger‐Liszkay, Anja
Summary The production of reactive oxygen species (ROS) is an unavoidable part of photosynthesis. Stress that accompanies high light levels and low CO2 availability putatively includes enhanced ROS production in the so‐called Mehler reaction. Such conditions are thought to encourage O2 to become an electron acceptor at photosystem I, producing the ROS superoxide anion radical (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj1xqn4pp" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />O2·−</alternatives>) and hydrogen peroxide (H2O2). In contrast, here it is shown in Chlamydomonas reinhardtii that CO2 depletion under high light levels lowered cellular H2O2 production, and that elevated CO2 levels increased H2O2 production. Using various photosynthetic and mitochondrial mutants of C. reinhardtii, the chloroplast was identified as the main source of elevated H2O2 production under high CO2 availability. High light levels under low CO2 availability induced photoprotective mechanisms called non‐photochemical quenching, or NPQ, including state transitions (qT) and high energy state quenching (qE). The qE‐deficient mutant npq4 produced more H2O2 than wild‐type cells under high light levels, although less so under high CO2 availability, whereas it demonstrated equal or greater enzymatic H2O2‐degrading capacity. The qT‐deficient mutant stt7‐9 produced the same H2O2 as wild‐type cells under high CO2 availability. Physiological levels of H2O2 were able to hinder qT and the induction of state 2, providing an explanation for why under high light levels and high CO2 availability wild‐type cells behaved like stt7‐9 cells stuck in state 1.